RESTRUCTURING SOCIAL WORK FIELD EDUCATION IN 21ST CENTURY CANADA: From Crisis Management to Sustainability - Ayala, Jessica; Drolet, Julie; Fulton, Amy; Hewson, Jennifer; Letkemann, Lorraine; Baynton, Myra; Elliott, Grace; Judge-Stasiak, Angela; Blaug, Carrie; Gérard Tétreault, Alice; Schweizer, Elizabeth (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2018)
Social work field education in Canada is in a state of crisis. For over two decades field education has faced increasing challenges and barriers within neoliberal contexts in higher education and the health and social services sector. These challenges have been magnified by an unprecedented growth in social work education programs and student enrolments, which has increased demand for field placements to an unsustainable level. Although some strategies for restructuring social work field education have been developed, to date little work has been done to formally identify, evaluate, and share information about these strategies across Canadian social work education programs. This article explores the current state of crisis from a solution-focused lens and describes three inter-related strategies to address critical problems with current models, practices, and processes. The strategies are presented as a Sustainability Model for Field Education. The results of a two-year study that sought to identify alternative delivery mechanisms for social work field education and promote sharing of information across social work education programs are discussed. A key recommendation is to restructure and move away from a crisis management approach by implementing strategies for enhancing the sustainability of field education.